298 Impact of colour-graded pictogram on medicine packages to caution against the risk of traffic crash. (1st September 2016) - Orriols, Ludivine; Luxcey, Audrey; Contrand, Benjamin; Gadegbeku, Blandine; Delorme, Bernard; Moore, Nicholas; Lagarde, Emmanuel
Abstract : Background: In France, a colour-graded pictogram is printed on the outer packaging of medicines according to their effect on driving performance, from level 1 (low risk) to level 3 (high risk). The aim of this study was to assess the impact of labelling benzodiazepines and z-hypnotics with level 2 or 3 pictograms on the risk of road traffic crash. Methods: Data from three French national databases were extracted and matched: the healthcare insurance database, police reports, and the police database of injurious crashes. Drivers involved in an injury crash in France, from July 2005 to December 2011, and identified by their national identifier were included. The study period was divided into 4 periods. The first period corresponded to a period before the colour-graded three-level pictogram was set up. The immediately subsequent period was used to estimate the impact of the introduction of the three-level pictogram. The two following time-periods were defined to assess any relapse in the potential impact of the pictogram. A case-control analysis comparing responsible versus non-responsible drivers was conducted. Results: 142, 763 drivers were included. Exposure to benzodiazepine anxiolytics (level 2 or 3) was associated with an increased risk of being responsible for a road traffic crash during the first period of the study (OR = 1.42 [1.24–1.62]). The association disappeared in the second period and became significant again during the third and the fourth period. The risk of being responsible for a crash increased in users of z-hypnotics (level 3) across the four periods (OR from 0.97 [0.81–1.17] to 1.32 [1.10–1.60]). Conclusions: Our results suggest that there has been a change in driving behaviour in benzodiazepine anxiolytic users after the implementation of the graded pictogram. However, there was a relapse immediately after. The increased risk associated with z-hypnotic use despite the presence of the higher level of pictogram calls for further preventive interventions.